Comparative Study of Fucose, Protein, Protein Bound Fucose and Protein Bound Hexose in Sera of Hyperprolactinemia Human Female and Healthy Female - Al-Taie, W.F.; Al-Iqabi, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was conducted in the specialized center of endocrinology and diabetic (AlKindy hospital from June 2004 to April 2005). Sera of 80 women (include 40 diagnosed Hyperprolactinemia (HPro) and 40 healthy women as control) were used to estimate some biochemical parameters which include prolactin (PRL),total fucose (TF), total protein (TP) and protein bound fucose (PBF), and protein bound hexose (PBHex),  also TP TF , TP PBF and TP PBHex   ratios. A significant elevation in TP and  PBHex, in sera of HPro patients compared to control was found while PBHex/TP ratio showed a slight non significant increase in sera of patients compared to control. On the other hand a significant decrease in TF, TF/TP and PBF/TP in sera of HPro compared to control was found. Total fucose level (TF) in sera of HPro compared to control are (6.54 ï‚± 1.52), (10.66 ï‚±4.00) mg/dL respectively. Protein bound fucose level (PBF) in sera of HPro compared to control are (3.88 ï‚± 1.25), (4.48ï‚± 1.63) mg/dL respectively, while protein bound hexose (PBHex) level in sera of HPro compared to control are (131.11ï‚±1.43) (123.64ï‚±0.497) mg/dL respectively. The significant increase in PRL levels in sera of patients was correlated with the significant reduced level of fucose in sera of patients compared to control. The low TF levels in patients could be due to the requirements of PRL variants to different ratios of monosaccharides including fucose and manose for glycosylation of PRL which may alter the biological activity in different species and variety of mammalian.